An Analysis of hegemonic masculinities in rameses and moses as seen in the ten commandments ( 1956 ) - Nazila Chiladati Rohmaniyati (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri, 2022)
et,1/ yna, c.1